Uji Antimikroba Ekstrak Segar Jahe-Jahean (Zingiberaceae) Terhadap Staphylococcus aureus, Escherichia coli dan Candida albicans - Kartika Indah Permata Sari; - Periadnadi; Nasril Nasir (Jurnal Biologi Universitas Andalas, 2013)
Seven species of Zingiberaceae were investigated for their antimicrobial activities against Staphylococcus aureus, Escherichia coli and Candida albicans. Extract of grinded rhizome was centrifuged at 10.000 rpm for five minutes. This study used completely randommized design in nested pattern with three replications. The first factor was the tested microbe and the second was the fresh extract of the ginger rhizome. The result showed that fresh extract of red ginger (Zingiber officinale var. Rubrum) gave the highest inhibition to the growth of S. aureus (15.83 mm) and E. coli (15.33 mm) while elephant ginger (Z. officinale var. Roscoe) gave the highest inhibition growth of C. albicans (10.7 mm).Key words: antimicrobial, ginger, microbial pathogen